A STUDY OF LEADERSHIP STRUCTURES IN AIYEDADE AND IMPLICATIONS FOR LOCAL INVOLVEMENT AND PARTICIPATION IN COMMUNITY DEVELOPMENT PROGRAMMES FOR HEALTH PROMOTION (1981)
The power and influence of traditional leaders over their subjects need to receive attention if they (the tradional leaders) are to assume new leadership roles as agents of comn1unity health workers in rallying general participation in community based programmes. The effectiveness of traditional leaders in these roles would vary from community to community. It would also depend to a large extent on how close or how remote they are connected w.ith decision-making in the community and the nature of community participation required. This is because the amount of power leaders exercise over their followers can be measured by their ability to make or influence decisions that affect the day-today activities of the subjects. Also, if participation of the general community is the goal of a community based health programme, then, the chiefs must be popular with more than half the population of the community. With regard to the power of the chiefs, one thing is important. It is this, new decision-making structures have been established in the Aiyedade community. But as power and influence have come to depend on other variables, (education, wealth, occupation) and the chiefs position is based on the traditional kinship relations, the power and influence of the chief will depend on his possession of some of these new variables. In the Aiyedade community, the chiefs almost match other leaders on occupational and social background but to the extent that he sometimes lacks the more modern forms of power base such as education and wealth his traditional monopoly of leadership is open to serious challenges. In the final analysis the degree of popularity a leader enjoys is a function of individual qualities of the leader as opposed to his position or status, qualities such as trustworthiness, service to the community and identification with the wishes and aspirations of the people lead to an individual's popularity with community members. But it is one thing being identified with these qualities and another thing being in a position to direct government resources to satisfy the needs of the people. The latter is the function of the key decision makers in the community. In the Aiyedade community the traditional leadership was not found to constitute the key decision - making body representing the central government. It was also observed that even though the traditional ruling elite was still popular, it had no monopoly of this popularity in the community. As the traditional leadership roles have been eroded by the newly emerged leaders it is no longer appropriate to organize popular following around the chiefs alone. Also as community based programmes may need resources other than the resources of community members alone, it is essential that persons controlling outside resources are involved jointly and simultaneously with other community members. This study then shows that if general community participation is the goal of the health educator in Aiyedade then the chief is only one of the leaders around whom popular Loll owing could be rallied.